Urgensi Pencantuman Regulasi Power Wheeling Ditinjau Dari Konsep Penguasaan Negara Dalam Konstitusi - Suswinarto, Gamos Cristo; K, Felicia Audrey (Universitas Widya Gama Malang, 2025)
This research aims to legally criticize the inclusion of the power wheeling scheme in the Draft Law on New and Renewable Energy, which has been debated in academic circles. This research uses the Normative juridical method, with conceptual and statutory approaches. The power wheeling scheme produces multiple seller and multiple buyer conditions, where private companies can not only produce electricity through private power plants (IPP), they can also sell electricity directly to the public, this is then a problem that needs to be studied legally, because if we look at electricity is (public utilities) concerning the livelihood of many people so that in determining the price of electricity it is not right to enter into a free market mechanism because the price will be determined by Supply and Demand, if Demand is high and supply is fixed then the price of electricity will automatically rise so that the mechanism is not able to guarantee the stability of the price of electricity and the power wheeling scheme will result in monopoly and electricity capitalism. Therefore, this mechanism should not be included in the Draft EBT Law because it contradicts Article 33 paragraph 2 of the 1945 Constitution which states that, Branches of production that control the livelihood of many people are controlled by the state. Therefore, through this research, the author would like to provide legal criticism of the power wheeling scheme, because basically a legal instrument must be able to guarantee and justify how the constitution should speak.